Aminobenzocoumarinylmethyl esters as photoactive precursors for the release of butyric acid1. (24th September 2015) - Soares, Ana M. S.; Hungerford, Graham; Costa, Susana P. G.; Gonçalves, M. Sameiro T.
<x xml:space="preserve">Abstract</x> The photorelease of butyric acid from new aminobenzocoumarin ester cages under UV/visible irradiation.